Н. В. Гоголь и театр - Гудушаури, Н. О. (My University, 2017)
У статті розглядається питання, пов'язані з метою написання Гоголем комедії "Ревізор", сприйняття її глядачами та критикою, звертається увага на своєрідність та унікальн 'ють форми і змісту твору як драми для читання на роль автора-оповідача, у якому звучить апофеоз театрального мистецтва з його великим громадсько-моральним значенням.
N. V. Gogol gave a high esteem to the theater as a chair tmm which you can say "a lot of good things for the country". For this purpose, the "Revisor" in his comedy has taken a hard, unruly missbn to openly state the shameful situation in Russia - the bribery that has been turned into a part of the mentality of the Russian official world. After the comedy presentation, Gogol writes an entirely original dramatic work - 'Theatrical Traffic after New Comedy Productbn", in which the covert "Revisor" is based on its first staging and which later evaluated itself as its own aesthetb credo. In the article "N. V. Gogol and Theater "is the purpose of creating these dramatic works. The uniqueness and uniqueness of the contents and shape of the work reveals the "theater movement... "is a dramatic drama. Here are the reactbns of viewers of different social layers in the view and analyzed the thread ofdiscussbn, which is justifbd by the contents of the final monologue of the author (narrator), where the apotheosis of the theatrical art is his great social-moral meaning.
Keywords: комедія; театр; comedy; theatre; the nucleus; positive hero